Analysis of Art Criticism from the Perspective of Big Data from the Perspective of All Media Communication of Film and Television Art. Issue 3 (October 2020) - Luo, Ru
Abstract: As a different art evaluation activity, art criticism has a very positive and powerful influence on the creators of art. With the advent of big data technology, the types of art criticism of film and television art from the perspective of all media are also changing correspondingly. The fragmentation of criticism form, the subjectivity of criticism content and the diversification of criticism subject have been discovered. However, the characteristics of these criticisms not only promote the prosperity of art criticism from the perspective of big data, but also bring a lot of negative effects to people. This paper briefly summarizes the concept of art criticism and the main characteristics of all media art criticism from the perspective of computer big data, and finally draws the corresponding conclusions.